A Dui Hua (对话) Standpoint to Multilingual Educational Theorizing - Haibo Shen (MDPI AG, 2017)
New forms of intellectual inequality have become evident with the internationalisation of higher degree researchers (HDRs) education, in particular theoretical dominance and dependency. However, the linguistically and theoretically based inequalities associated with local/global currents of standardized monolingual English HDRs education are gradually opening up to scholarly debates. In the field of education, bilingual HDRs have the potential disposition, and some have the capabilities for multilingual theorizing. Some make use of their knowledge of more than one language to extend the possibilities for theorizing educational phenomena or otherwise naming and making sense of problems. This multilingual theorizing may provide another path to transform the problems with uniformized, Anglophone HDRs education. With this concern, this paper reconsiders the universalisation of Euro-American theories through their embodiment in monolingual English in HDR education. A Dui Hua (对话) standpoint to other languages and theoretical knowledge is outlined and debated to highlight the divergences of languages and thoughts. Thus this paper probes into the possibilities of multilingual educational theorizing, whereby bilingual HDRs generate original conceptual tools that benefit the wider educational research community.